A LAGGING AFFAIR: JUDICIAL BRANCH AND HISTORICAL STUDIES ON COSTA - Cascante Segura, Carlos Humberto (2022)
This paper aims to present a state of art on research about Judicial Branch and Justice Administration in Costa Rica. It compares the sources and methods used by the various authors who have worked on this subject. It is concluded that the lack of systematic and continuous studies on Judicial Branch are especially notorious for the Costa Rican 19th century, likewise, research on justice administration as instrument for social control have been a predominant issue. However, research on institutional development, understood as the normative progression, bureaucratic consolidation process and political legitimation discourses conformation; has been scarce. From these institutionalization components, studies on legal norms with regulates Judicial Branch have been predominant, but, in general, these ones had suffered for the lack of contextualization of the social phenomena that explain the existence of such legal norms.